THROUGH CLASSROOM ACTION RESEARCH TRAINING AND SCIENTIFIC ARTICLE WRITING ASSISTANCE - Igo Samuel Leton (Universitas Borneo Tarakan, 2022)
This Community Service aims to train teachers in conducting Classroom Action Research and assist them in writing scientific articles resulting from CAR. The implementation of this training and mentoring activity was carried out in a blended (online and offline) manner which was attended by 55 teachers with details: 11 Kindergarten teachers, 21 teachers at the elementary school level, 12 teachers at the junior high school level, and 11 teachers at the elementary school level. High School level. Based on the results of observations and discussions with partners, the Community Service Team carried out assistance activities in two stages, namely: 1) strengthening the concept of CAR and Scientific Work; and 2) assistance in writing CAR scientific papers. The output of this activity is an increase in the knowledge and skills of teachers in doing CAR. Based on the results of the evaluation carried out, the teachers felt very helpful with this training and mentoring activity. In addition to increasing teachers' knowledge of CAR concepts, this activity also improves the skills of teachers in designing and implementing CAR through useful activities, setting goals and benefits, making theoretical frameworks, selecting methods, compiling instruments, collecting and analyzing data, and writing articles